Chitinase‐resistant hydrophilic symbiotic factors secreted by Frankia activate both Ca2+ spiking and NIN gene expression in the actinorhizal plant Casuarina glauca. Issue 1 (20th October 2015) - Chabaud, Mireille; Gherbi, Hassen; Pirolles, Elodie; Vaissayre, Virginie; Fournier, Joëlle; Moukouanga, Daniel; Franche, Claudine; Bogusz, Didier; Tisa, Louis S.; Barker, David G.; Svistoonoff, Sergio
Summary: Although it is now well‐established that decorated lipo‐chitooligosaccharide Nod factors are the key rhizobial signals which initiate infection/nodulation in host legume species, the identity of the equivalent microbial signaling molecules in the Frankia /actinorhizal association remains elusive. With the objective of identifying Frankia symbiotic factors we present a novel approach based on both molecular and cellular pre‐infection reporters expressed in the model actinorhizal species Casuarina glauca . By introducing the nuclear‐localized cameleon Nup‐YC2.1 into Casuarina glauca we show that cell‐free culture supernatants of the compatible Frankia CcI3 strain are able to elicit sustained high frequency Ca 2+ spiking in host root hairs. Furthermore, an excellent correlation exists between the triggering of nuclear Ca 2+ spiking and the transcriptional activation of the Pro CgNIN : GFP reporter as a function of the Frankia strain tested. These two pre‐infection symbiotic responses have been used in combination to show that the signal molecules present in the Frankia CcI3 supernatant are hydrophilic, of low molecular weight and resistant to chitinase degradation. In conclusion, the biologically active symbiotic signals secreted by Frankia appear to be chemically distinct from the currently known chitin‐based rhizobial/arbuscular mycorrhizal signaling molecules. Convenient bioassays in Casuarina glauca are now available for their full characterization.